A hydro-mechanical coupled solution for electro-osmotic consolidation in unsaturated soils considering the decrease in effective voltage with time. (May 2021) - Wang, Liujiang; Shen, Chaomin; Liu, Sihong; Alonso, Eduardo; Huang, Penghua
Abstract: For electro-osmotic consolidation in unsaturated soils, coupled deformation, inconsistent changes in hydraulic conductivity and electro-osmotic permeability with matric suction, and a decrease in effective voltage with time occur simultaneously. To consider all of these processes, an analytical solution was proposed. The time-stepping method was adopted in the calculation of the solution to depict the nonlinear change in shrinkage deformation with matric suction. The accuracy of the proposed analytical solution was validated by comparison with results from laboratory tests and from a previously presented solution without considering coupled deformation. Then, a parametric study was conducted. The results indicate that the dissipation of the pore water pressure is slow when considering coupled deformation, but a large volume of water is discharged in the end, especially for soils with a large volumetric shrinkage index Cm . A larger final negative pore water pressure and discharged water can be predicted by considering the inconsistent changes in hydraulic conductivity and electro-osmotic permeability. Finally, with the consideration of the decrease in effective voltage over time, both the maximum negative pore water pressure and final drainage decrease, which is consistent with field observations.